2020
DOI: 10.1111/and.13759
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of intracavernosal alprostadil and oral clomiphene citrate combination treatment in penile vasculogenic erectile dysfunction patients accompanied by late‐onset hypogonadism

Abstract: Erectile dysfunction (ED) refers to difficulty in starting and maintaining an adequate erection for satisfactory sexual performance and the stability of this condition (Burnett et al., 2018). The estimated prevalence of ED in men > 40 years of age is almost 50% (Bella, Lee, Carrier, Benard, & Brock, 2015). Different therapeutic agents have been developed for ED treatment, and their effect mechanism depends on the understanding of erection physiology. In ED treatment-resistant patients, lifestyle changes as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…20 In different studies, it was also found that clomiphene combined with PDE-5 inhibitors improved the treatment response. 21,22 In this study, in accordance with the literature, intracavernosal alprostadil treatment resulted in significant improvement in all IIEF-15 scores and degree of erection.…”
Section: Resultssupporting
confidence: 89%
“…20 In different studies, it was also found that clomiphene combined with PDE-5 inhibitors improved the treatment response. 21,22 In this study, in accordance with the literature, intracavernosal alprostadil treatment resulted in significant improvement in all IIEF-15 scores and degree of erection.…”
Section: Resultssupporting
confidence: 89%
“…One study reported an incidence of pain in the injection site or during erection of 11%, hematoma or ecchymosis at 1.5%, priapism (defined as a painful erection exceeding 4 h in duration) at 1.5%, and penile plaque at 2% (21). Another study reported penile pain and priapism at a rate of 6.4% (22). Bearelly et al reported that plaque or scar formation was 10%, pain 2%, ecchymosis <1%, irritability <1%, headache <1% and tissue damage <1% (17).…”
Section: Discussionmentioning
confidence: 99%